A new reading of the desert anthem Arab Lamia (Journal of the College of Basic Education, 2023)
Al-Shanfari Amr bin Malik Al-Azdi from Bani Al-Harith bin Rabi’a, a poet known for his poem of Arab illiteracy, the anthem of the desert, the passion of the ears of its recipient, and he played a string that his opponents sang before his disciples, after he explored his own world, which he did not disclose to them his secret, and his opponent could not gain from him as long as he was among those So I went back to this nasheed to settle it and read what lies in it anew that no one else had experienced, so the nasheed became a sob once, a cry a second time, a third rebellion, a protest, harshness, and patience to achieve the goal. He sought and relied on God.